Mode of action studies confirm on-target engagement of lysyl-tRNA synthetase inhibitor and lead to new selection marker for Cryptosporidium - Hanna, Jack C.; Corpas-Lopez, Victor; Seizova, Simona; Colon, Beatrice L.; Bacchetti, Ross; Hall, Grant M. J.; Sands, Emma M.; Robinson, Lee; Baragaña, Beatriz; Wyllie, Susan; Pawlowic, Mattie C. (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Cryptosporidiosis is a leading cause of diarrheal-associated morbidity and mortality, predominantly affecting children under 5 years old in low-and-middle-income countries. There is no effective treatment and no vaccine. New therapeutics are emerging from drug discovery efforts. It is critical that mode of action studies are performed alongside drug discovery to ensure the best clinical outcomes. Unfortunately, technology to identify and validate drug targets for Cryptosporidium is severely lacking. Methods We used C. parvum lysyl-tRNA synthetase (CpKRS) and DDD01510706 as a target-compound pair to develop both chemical and genetic tools for mode of action studies for Cryptosporidium. We adapted thermal proteome profiling (TPP) for Cryptosporidium, an unbiased approach for target identification. Results Using TPP we identified the molecular target of DDD01510706 and confirm that it is CpKRS. Genetic tools confirm that CpKRS is expressed throughout the life cycle and that this target is essential for parasite survival. Parasites genetically modified to over-express CpKRS or parasites with a mutation at the compound-binding site are resistant to treatment with DDD01510706. We leveraged these mutations to generate a second drug selection marker for genetic modification of Cryptosporidium, KRSR. This second selection marker is interchangeable with the original selection marker, NeoR, and expands the range of reverse genetic approaches available to study parasite biology. Due to the sexual nature of the Cryptosporidium life cycle, parental strains containing different drug selection markers can be crossed in vivo. Discussion Selection with both drug markers produces highly efficient genetic crosses (>99% hybrid progeny), paving the way for forward genetics approaches in Cryptosporidium.